.63 i mean it is not that hard
First do 4.04 mil - 3.66 mil to get .38 mil (which is 380 thousand) then divide 380,000/10 to get answer J. 38,000. Hope this helped
Answer:
-2
Step-by-step explanation:
g(3)= 2(3)-7
g(3)= 6-7
g(3)= -1
f(g(3))= 4(-1)+2
f(g(3))= -4+2
f(g(3))= -2
The expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Complete question.
Simplify the expression to a + bi form:
(-2 - 6i)-(-2-4i)
Square root of any negative number are expressed as a complex number. For example i = √-1
Complex numbers are generally written in the format z = x+iy
Given the expression (-2 - 6i)-(-2-4i)), in expansion:
(-2 - 6i)-(-2-4i)
= -2 - 6i + 2+4i
Collect the like terms
= (-2 + 2) - 6i + 4i
= 0 - 2i
Therefore the expression (-2 - 6i)-(-2-4i) to a + bi form is 0 - 2i.
Learn more on complex number here: brainly.com/question/12375854